Factors affecting advance directives completion among older adults in Korea - Seunghye Choi; Hana Ko (Frontiers Media S.A., 2024)
ObjectiveAdvance directives (ADs) provide an opportunity for patients to enhance the quality of their end-of-life care and prepare for a dignified death by deciding treatment plans. The purpose of this study was to explore the multiple factors that influence the advance directives completion among older adults in South Korea.MethodsThis was a secondary analysis of a cross-sectional study of 9,920 older adults. The differences in ADs based on subjects' sociodemographic characteristics, health-related characteristics, and attitude toward death were tested using the chi-squared and t-test. A multinomial logistic regression model was used to identify the influencing factor of ADs.ResultsThe number of chronic diseases, number of prescribed medications, depression, insomnia, suicide intention, and hearing, vision, or chewing discomfort were higher in the ADs group compared to the non-ADs group. The influencing factors of the signing of ADs included men sex, higher education level, exercise, death preparation education, lower awareness of dying-well, and experience of fracture.ConclusionInformation dissemination regarding ADs should be promoted and relevant authorities should consider multiple options to improve the physical and psychological health of older adults, as well as their attitude toward death to increase the ADs completion rate.